Piezoelectric Ultrasound MEMS Transducers for Fingerprint Recognition - 정수영; 박진수; 김민석; 장호원; 이병철; 백승협 (한국센서학회, 2022)
As mobile electronics become smarter, higher-level security systems are necessary to protect private information and property from hackers. For this, biometric authentication systems have been widely studied, where the recognition of unique biological traits of an individual, such as the face, iris, fingerprint, and voice, is required to operate the device. Among them, ultrasound fingerprint imaging technology using piezoelectric materials is one of the most promising approaches adopted by Samsung Galaxy smartphones. In this review, we summarize the recent progress on piezoelectric ultrasound micro-electro-mechanical systems (MEMS) transducers with various piezoelectric materials and provide insights to achieve the highest-level biometric authentication system for mobile electronics.